Seismic analyses of a R/C building: study of a retrofitting solution - Varum, H. (2012)
The preliminary experimental results from the tests on a 4-storey R/C frame structure are presented and discussed. The full-scale model is representative of the common practice of 40~50 years ago in most south European countries. Special attention is devoted to the study of a retrofitting solution based on bracing and rubber dissipaters, which intends to increase stiffness and damping reducing consequently the earthquake deformation demands.